2004
DOI: 10.2188/jea.14.143
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Conditions in Patients with Parkinson's Disease

Abstract: AnalysesWe compared the case group with the control group using the unconditional logistic regression model 17 adjusted for sex and age. The adjusted odds ratio (OR) and its 95% confidence interval (CI) were estimated. We also conducted stratified analysis by sex and age group using this model. The 2 test and the Cochran-MantelHaenzel test were used for simple and stratified analyses of knowledge of oral health among PD patients, respectively. Tests of statistical significance were based on two-sided P values,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 7 publications
6
82
0
8
Order By: Relevance
“…A recent case control study in Japan showed that patients with PD have fewer teeth and also did not clean their dentures as regularly as controls [14]. Accordingly, severe dental problems were reported in all participants of a Greek survey [2].On the other hand,in a small group of Parkinson's disease outpatients, patients had more teeth compared with controls [6].Kennedy and co-workers investigated dental plaques in 14 patients and 14 controls.Although there were only minor differences in oral microflora, Parkinson's disease patients showed significantly more pronounced mucositis [10].…”
Section: Discussionmentioning
confidence: 99%
“…A recent case control study in Japan showed that patients with PD have fewer teeth and also did not clean their dentures as regularly as controls [14]. Accordingly, severe dental problems were reported in all participants of a Greek survey [2].On the other hand,in a small group of Parkinson's disease outpatients, patients had more teeth compared with controls [6].Kennedy and co-workers investigated dental plaques in 14 patients and 14 controls.Although there were only minor differences in oral microflora, Parkinson's disease patients showed significantly more pronounced mucositis [10].…”
Section: Discussionmentioning
confidence: 99%
“…For PD patients, loss of neuromuscular control must be considered a major contributory factor in the loss of stability of complete dentures [15]. Previous studies [15,16] reported that PD patients have chewing difficulties, denture discomfort [16], and problems such as poor denture control [15]. Impaired masticatory performance [13], coupled with denture-related problems, may compound the existing difficulties that PD patients have in eating and swallowing [17].…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Oral health of patients with Parkinson's disease (PD) has also been studied with contradictory results. [9][10][11][12][13] Patients with PD may experience difficulty in maintaining oral hygiene due to several factors: motor impairment, dysphagia, apathy, depression, dementia, hypersialorrhea, xerostomia and medication. Some publications have reported a high incidence of patients with PD with deteriorating dental status, [9][10][11] whereas others have reported a smaller chance of patients with PD developing tooth loss and caries.…”
Section: Introductionmentioning
confidence: 99%